Onset of double-diffusive convection of a sparsely packed micropolar fluid in a porous medium layer saturated with a nanofluid; Microfluidics and Nanofluidics; Vol. 21, iss. 7 - Umavathi Ja. C. Jawali (2017, 2017)
Title screen